Eliciting guilt in virtual reality games: interplay of self-attribution, presence, and morality - Ahn, Changhyun; Noh, Ghee Young (Frontiers in Psychology, 2024)
This study examines the complex psychological mechanisms at play in virtual reality games, specifically the interplay between character morality, self-attribution, presence, guilt, and their collective influence on player enjoyment. Drawing on Zillmann and Cantor's (1976) Affective Disposition Theory, this study hypothesizes that players' moral judgments of characters significantly influence their engagement with and enjoyment of virtual reality narratives. The immersive nature of virtual reality provides a unique digital experience through which to understand the psychological effects of gaming, particularly in terms of how players perceive their actions in virtual environments, and their resulting emotional consequences. This study conducted a post-test between-subjects experiment with 97 participants to explore how character morality influences guilt through the mediation of self-attribution, and how these elements affect players' sense of presence and overall enjoyment. Results revealed that self-attribution serves as a significant mediator between character morality and guilt. Furthermore, the results noted the critical role of presence in enhancing enjoyment, while a stronger sense of 'being there' in virtual reality games amplifies the emotional weight of players' moral choices. As such, this study highlights the full mediating effect of selfattribution in the virtual reality gaming context, thereby intensifying players' emotional responses to moral dilemmas. These findings have profound implications for virtual reality game design and ethics, suggesting that designers should carefully consider the moral implications of game narratives and character actions. By creating scenarios that encourage players to reflect on the morality of their actions, virtual reality games can offer richer and more emotionally engaging experiences that can potentially foster greater ethical sensitivity.